Heat Resistance of Listeria monocytogenes in Dairy Matrices Involved in Mozzarella di Bufala Campana PDO Cheese - Ricci, Annalisa; Alinovi, Marcello; Martelli, Francesco; Bernini, Valentina; Garofalo, Alessandro; Perna, Giampiero; Neviani, Erasmo; Mucchetti, Germano (Frontiers in Microbiology, 2021)
The presence of Listeria monocytogenes in Mozzarella di Bufala Campana Protected Designation of Origin cheeses may depend on curd stretching conditions and post contaminations before packaging. To avoid cross-contamination, thermal treatment of water, brines and covering liquid may become necessary. The present study aimed to improve knowledge about L. monocytogenes thermal resistance focusing on the influence of some cheese making operations, namely curd stretching and heat treatment of fluids in contact with cheese after molding, in order to improve the safety of the cheese, optimize efficacy and sustainability of the processes. Moreover, the role that cheese curd stretching plays in L. monocytogenes inactivation was discussed. The 12 tested strains showed a very heterogeneous heat resistance that ranged from 7 to less than 1 Log10 Cfu/mL reduction after 8 min at 60°C. D-values (decimal reduction times) and z-values (thermal resistance constant) calculated for the most heat resistant strain among 60 and 70°C were highly affected by the matrix and, in particular, heat resistance noticeably increased in drained cheese curd. As cheese curd stretching is not an isothermal process, to simulate the overall lethal effect of an industrial process a secondary model was built. The lethal effect of the process was estimated around 4 Log10 reductions. The data provided may be useful for fresh pasta filata cheese producers in determining appropriate processing durations and temperatures for producing safe cheeses.